(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics of patients with premature ejaculation; and to evaluate treatment outcomes using a combination regimen of Dapoxetine 60 mg and Tadalafil 10 mg. Subjects and methods: 55 patients with premature ejaculation who met the inclusion criteria were enrolled in the study. The study was a descriptive cross-sectional study of the following characteristics: age, characteristics of premature ejaculation, comorbidities, PEDT score, SHIM score, QoL score, and the effect of the combination therapy regimen. Results: The mean age was 34.47 ± 8.92 (18-65 years), with those under 40 accounting for 50.09%. Pre-treatment ejaculation time was 1.78 ± 0.42 minutes (1-2 minutes). Prostate size was 13.76 ± 2.7 grams (10-23 grams); among the comorbidities associated with premature ejaculation, varicocele was the most common (21.82%). Pre-treatment total PEDT score was 15.22 ± 2.25 points; QoL score: 4.87 ± 0.88 points (p < 0.05); average SHIM score was 18.11 ± 1.65 points, with no significant difference between age groups; after treatment, PEDT and SHIM scores showed statistically significant differences with p < 0.05. The assessment of quality of life after treatment showed significant improvement, with 100% of patients satisfied with the treatment results. The pre- and post-treatment QoL scores showed a statistically significant difference (p < 0.05). Conclusion: Premature ejaculation significantly impacts patients’ quality of life. Combining Dapoxetine 60 mg with Tadalafil 10 mg in treatment improved premature ejaculation, increased SHIM scores, and statistically significantly improved quality of life. Due to the small number of patients in the study and the short follow-up period, further study and evaluation are needed.